2004
DOI: 10.1186/1475-925x-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of EEG signals at different mental states

Abstract: BackgroundThe EEG (Electroencephalogram) is a representative signal containing information about the condition of the brain. The shape of the wave may contain useful information about the state of the brain. However, the human observer can not directly monitor these subtle details. Besides, since bio-signals are highly subjective, the symptoms may appear at random in the time scale. Therefore, the EEG signal parameters, extracted and analyzed using computers, are highly useful in diagnostics. This work discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(102 citation statements)
references
References 41 publications
0
101
0
1
Order By: Relevance
“…Similarly, a low and regular neuronal activity during an emotional state of calm has also been previously reported by works dealing with different relaxing therapies. Indeed, nonlinear indices like Lyapunov exponents or SE have been able to notice significant decreases in brain activation during relaxing music, foot reflexology and meditation [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a low and regular neuronal activity during an emotional state of calm has also been previously reported by works dealing with different relaxing therapies. Indeed, nonlinear indices like Lyapunov exponents or SE have been able to notice significant decreases in brain activation during relaxing music, foot reflexology and meditation [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Yoo et al reported a difference in neural activity between real and sham acupunctural stimulation in the primary and secondary somatosensory cortex [10]. As for touch massage, including reflexology, a relaxing effect of reflexology was observed using electroencephalography (EEG) [11], pleasant touch massage induced activation of the pregenual anterior cingulate cortex [12], and reflexological treatments affected resting-state neural activity in the retrosplenial/posterior cingulated cortex [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the literature are related to the analysis of EEG signals associated with some pathology (Bennys et al, 2001;Bonanni et al, 2008;Dauwels et al, 2011;Faust et al, 2007;Natarajan et al, 2004) which demonstrates the lack of studies with the purpose of understanding the complex relationship between the EEG signal of healthy subjects and the aging. This study included only healthy subjects.…”
Section: Resultsmentioning
confidence: 99%